PENINGKATAN EKONOMI MASYARAKAT MELALUI PEMANFAATAN POTENSI LOKAL KEMIRI - Luciany, Yohanes Paulus; Jeja, Oktavianus Gore; Ragha, Martina Yasinta R (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Watuneso Subdistrict has great potential in developing an economy based on local resources, especially candlenuts. Candlenut is a superior commodity and is one of the sources of livelihood for the people of Watuneso Village. However, the people of Watuneso Village do not yet know how to process candlenuts further, which can increase the selling price of these candlenuts. This service is carried out to increase community empowerment efforts through training in processing candlenuts into candlenut oil, which has many benefits and to improve the economy of the Watuneso community through optimizing the local potential of candlenuts. It is hoped that this diversification activity in processed candlenut products will improve the economy, considering that the price of candlenut oil on the market is quite high. The training process includes theory and direct practice and involves active community participation. The results show that the training is effective in increasing people's knowledge, skills and motivation. Apart from that, candlenut oil production has the potential to increase the economic income of the community in Watuneso Village.